Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/978-3-319-05936-5_3
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Plant Associated Actinobacteria

Abstract: The phylum Actinobacteria encompasses Gram-positive bacteria with a high DNA G+C. In soils, they present multiple lifestyles: rhizosphere saprophytes, endophytes, facultative symbionts and obligate phytopathogens. They play either beneficial or adverse effects towards plants. Numerous studies focused on their taxonomy and preservation. Also, adequate strategies were developed to enable their isolation. Phenotypically, the Actinobacteria is one of the most diverse phyla within bacteria. Their presence was once … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 398 publications
0
8
0
Order By: Relevance
“…The three selected strains were tested in vitro for properties that are known to be important for plant growth promoting activities of bacteria, such as the production of siderophores, solubilization of inorganic phosphate, phytohormone levels etc. Overall, these suggested that all three strains can solubilize phosphate and produce siderophores, proteases, and IAA, which are also typical of plant-associated Actinobacteria, and have been related to plant-growth promotion (Nimnoi et al, 2010; Bouizgarne and Aouamar, 2014; Carvalho et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…The three selected strains were tested in vitro for properties that are known to be important for plant growth promoting activities of bacteria, such as the production of siderophores, solubilization of inorganic phosphate, phytohormone levels etc. Overall, these suggested that all three strains can solubilize phosphate and produce siderophores, proteases, and IAA, which are also typical of plant-associated Actinobacteria, and have been related to plant-growth promotion (Nimnoi et al, 2010; Bouizgarne and Aouamar, 2014; Carvalho et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…Actinobacteria represent approximately 20–30% of the rhizospheric microbial community (Bouizgarne and Ben Aouamar, 2014 ). They are Gram-positive and show a wide morphological spectrum ranging from unicellular organisms to branching filaments that form a mycelium.…”
Section: Plant-associated Actinobacteriamentioning
confidence: 99%
“…The rhizospheric soil is dominated by the diverse bacterial communities. 24 , 25 , 26 , 27 , 28 These bacterial communities are involved in developing the mutual interaction with plant roots and thus improve the growth and development of plants through various mechanisms. 19 , 29 , 30 , 31 These mechanisms include biological nitrogen fixation (BNF), production of growth hormones, improvement in the availability of the nutrients particularly phosphorous, and the bio-control of plant pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…The rhizospheric soil is dominated by the diverse bacterial communities 24, 25, 26, 27, 28. These bacterial communities are involved in developing the mutual interaction with plant roots and thus improve the growth and development of plants through various mechanisms 19, 29, 30, 31.…”
Section: Introductionmentioning
confidence: 99%